Technologies for the Use of Innovative Teaching Aids in Teaching Economic and Social Geography - Nurmatjonovna, Quldasheva Makhmuda (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the topical issues of teaching the subject of economic and social geography. Information on the technologies of approach in the teaching of science, innovative teaching assignments, examples of innovative teaching assignments developed in science are highlighted.